ANALISIS YURIDIS TERHADAP KASUS-KASUS MALPRAKTIK OLEH TENAGA KESEHATAN NON-DOKTER DI RUMAH SAKIT - Abram Sahing; Rina Arum Prastyanti; Uli Kristiani Saragih (Universitas Duta Bangsa Surakarta, 2025)
Medical malpractice by non-physician health workers is a significant issue in Indonesia's healthcare system. Nurses and midwives, whether acting independently or under delegation from physicians, are at risk of exceeding their authority, which can result in legal consequences. This study aims to analyze the forms of malpractice committed by non-doctor health personnel, the legal regulations governing such acts, and the applicable legal liabilities. The research uses a normative juridical method with statutory, case, and conceptual approaches. Findings indicate regulatory weaknesses, overlapping institutional authority, and insufficient legal education among health workers, leading to ineffective handling of malpractice cases. Legal reform is needed through technical SOP formulation, strengthening of medical record systems, and continuous legal education for non-physician health personnel.